L'immunité constitutionnelle des corporations provinciales - Lavoie, Chantal (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
This paper purports to examine whether provincially incorporated corporations are immune from federal laws affecting their status and essential powers. Federal corporations enjoy such an immunity in respect to provincial laws. After considering the nature of the provincial power of incorporation, we focus on the basis of the status and essential powers immunity. Federal immunity is either founded on the paramountcy and the inoperability of the law or on the exclusiveness and the inapplicability of the law (reading-down doctrine). The latter hypothesis would allow provincial companies to benefit from an immunity analogous to the one recognized for federal companies. Furthermore, such an immunity will render certain, but not all, federal laws inapplicable to provincial corporations. A distinction must be drawn between a law pertaining to provincial corporate matters and a law regulating business activities. In the latter case, the provincial corporation must observe this law since it does not impair its status and essential powers.